2023
DOI: 10.11591/ijphs.v12i1.22002
|View full text |Cite
|
Sign up to set email alerts
|

Control of industrial major accident hazard regulation in Malaysia: second decade in examination

Abstract: The Control of Industrial Major Accident Hazards (CIMAH) regulations was introduced in 1996 to regulate workplaces with hazardous chemicals in their facilities. The Regulations provide a minimum standard to ensure precautionary measures related to major hazard risks are taken. Although the Regulations have been enforced for more than two decades in Malaysia, there have been limited efforts to review related information, trends and data since its inception. The study aimed to provide an overview of the position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…9 Similar qualitative method designs of document analysis approaches have been used in previous studies. [10][11][12] The majority of the information used in this study was obtained from documents held by DOSH, the regulatory body responsible for overseeing MHCP registration status in Malaysia. The documents were divided into two categories: (1) published documents, such as annual reports, website and online portal information, and departmental statistical data, which are available to the public through DOSH publications; and ( 2…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Similar qualitative method designs of document analysis approaches have been used in previous studies. [10][11][12] The majority of the information used in this study was obtained from documents held by DOSH, the regulatory body responsible for overseeing MHCP registration status in Malaysia. The documents were divided into two categories: (1) published documents, such as annual reports, website and online portal information, and departmental statistical data, which are available to the public through DOSH publications; and ( 2…”
Section: Methodsmentioning
confidence: 99%
“…The number of registered MHIs increased almost sixfold from 1996 to 2021. 12 The scenario creates a profession. [35][36][37] In a descriptive study that spans over 6 years, involving more than 1000 professionals in various fields, the researchers found that one of the main motivators for professionals to pursue certification is 'career growth' .…”
Section: Registrationmentioning
confidence: 99%
“…Conveyor belt -major hazard incidents, SME's operating procedure and discuss the process of hazard analysis, training, and emergency response planning [15].…”
Section: Cement Manufacturermentioning
confidence: 99%